Odpowiedź:
zad 1
[tex]a)-2\frac{1}{4}*2\frac{1}{3}=-\frac{9}{4}*\frac{7}{3}=-\frac{21}{4}=-5\frac{1}{4}\\\\b)(-7\frac{1}{5}):(-3\frac{1}{5})=(-\frac{36}{5})*(-\frac{5}{16})=\frac{36}{16}=2\frac{1}{4}\\\\c)(-1,4)*(-5,07)=(-\frac{14}{10})*(-\frac{507}{100})=\frac{7098}{1000}=7\frac{98}{1000}=7\frac{49}{500}\\\\d)0,056:(-0,7)=\frac{56}{1000}*(-\frac{10}{7})=-\frac{8}{100}=-\frac{2}{25}[/tex]
zad 2
[tex]a)63-36:(43-34)=27:9=3\\\\b)[17-4-(-2)^3]*(-3)^2=[17-4-(-8)]*9=(17-4+8)*9=21*9=189[/tex]
zad 3
a) 534,4
b) 801,965
c) 4000